Implementasi Sistem Informasi IMPLEMENTASI MODEL WATERFALL DALAM SISTEM INFORMASI PEMINJAMAN BUKU PADA PERPUSTAKAAN SEKOLAH - Dahlia, Dahlia; Lestari, Endah Wiji; Leliyanah, Leliyanah (INSTITUT TEKNOLOGI DAN BISNIS INDOBARU NASIONAL, 2022)
In the era of technology that has developed rapidly today, of course, the use of computers can help human work to be faster, and more efficient, of course with the right hardware and software support. SMK 17 August 1945 is a vocational high school which consists of 2 majors, namely Administration and Book Management and Business Administration. At this time, book borrowing activities that occur in school libraries still use large books in recording borrowing and returning books, as well as in the process of collecting incoming books or new books to recording damaged books, until the reporting process is still done conventionally. Allows for errors in the recording process, data loss due to shabby old files or negligence of officers in terms of fines if there is a delay in returning books by students. Problems that occur during the process of borrowing and returning books in the library at this time, library information systems that can manage book borrowing data that can support and provide good services for staff, members and library visitors. Application of the waterfall model on software requirements, software system design, implementation and unit testing. While the information system design method will be described using a unified modeling language (UML), namely use case diagrams, activity diagrams, sequence diagrams and class diagrams.